Testing stochastic cycles in macroeconomic time series - Luis A. Gil-Ala\~na (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
A particular version of the tests of Robinson (1994) for testing stochastic cycles in macroeconomic time series is proposed in this article. The tests have a standard limit distribution and are easy to implement in raw time series. A Monte Carlo experiment is conducted, studying the size and the power of the tests against different alternatives, and the results are compared with those based on other tests. An empirical application using historical U.S. annual data is also carried out at the end of the article.
urn:nbn:de:kobv:11-10047968
Keywords: C22; 330; stochastic cycles; fractional roots; unit root cycles